Property valuation under uncertain market conditions: a case of the Lagos property market - Oladokun, Sunday Olarinre (Department of Construction Economics and Management, 2023)
This research seeks to provide an understanding of how the nature of the property market affects the valuation practice and how valuers manage such conditions during the valuation process. Specifically, the study investigates challenges that uncertain conditions of the Lagos property market pose to valuers and how valuers navigate a path through these challenges. This is with a view to providing a theoretical explanation for valuers' behaviour in an uncertain environment. The rationale for the study is that valuers' behaviour is influenced by the nature of the environment where they operate; however, there is yet to be a clear understanding of how valuers manage the conditions of property markets fraught with high uncertainty. The study pursues five objectives, namely, an examination of the nature of the Lagos property market as it relates to property valuation, an assessment of the nature of challenges valuers are exposed to within the Lagos property market and an investigation of how valuers manage the challenges of the uncertain nature of the Lagos property market. Others are an analysis of the existing real estate education in Nigeria to establish how it prepares valuers for the nature of the market they operate and a proposal of a framework for a better understanding of valuers' behaviour in an uncertain environment. Two working propositions were set for this study in relation to these objectives. Firstly, it was proposed that the Lagos property market exhibits a high level of uncertainty which poses challenges to property valuation practice. Secondly, it was proposed that in dealing with the challenges of the market, valuers would put up certain coping strategies, which can be understood through their cost minimisation behaviour. The study employs an exploratory sequential mixed methods research approach where qualitative and quantitative data were collected sequentially from multiple sources. Specifically, qualitative data were extracted from expert valuers using semi-structured interviews, while quantitative data were extracted from professional valuers and final-year students of tertiary institutions using questionnaires. Interview data were analysed using thematic analysis, while data extracted through questionnaires were analysed using descriptive and inferential statistic tools. Furthermore, this research explored the theoretical lens of Transaction Cost Economy (TCE) to explore the understanding of valuers' behaviour in an uncertain market. The study finds that the Lagos property market is characterised by features that directly affect the valuation practice. The market characteristics include the lack of a formal database of market transactions, weak institutions/corrupt property rights registration system, the dominance of valuation for mortgage purposes, and an improved standardisation and internationalisation of professional services. The shows that the nature of the market presents uncertain conditions and poses peculiar challenges to valuers. The study also finds that valuers put up various strategies to manage the challenges. The study established that while some of the identified valuers' coping strategies are logical and expected, others seem counterintuitive and unprofessional. However, the coping strategies are contextual in nature, as they are based on valuers' understanding of the nature of the market. The study also finds that gaps exist between academic training and the practice of valuation in Nigeria. That is, valuers' academic training does not reflect the actual experience of valuers in the market. Thus, the results partially confirm the first proposition and substantially confirm the second proposition. Overall, the study concludes that the uncertain nature of the Lagos property market opens valuers to several forms of coping strategies influenced by their understanding of the market environment and academic training. Assessing valuers' behaviour through the lens of TCE, the study demonstrates that while some valuers' coping strategies reduce valuation uncertainty, others increase the uncertainty and bias in valuation. It is also concluded that the provisions of TCE more accurately reflect the actual experience of valuers in a volatile and uncertain market. This study makes a number of contributions to knowledge. Specifically, it contributes to theory by expanding on the principles of TCE and applying them to the property market and valuation practice. It contributes to policy development by offering insights that can help develop improved ethical and professional standards. Lastly, the study contributes to the empirical literature by providing a deeper understanding of how valuers utilise heuristics in their decision-making processes.